DRIS Norms and Sufficiency Ranges for Persimmon ‘Rojo Brillante’ Grown under Mediterranean Conditions in Spain - Julia Morales; Isabel Rodríguez-Carretero; Belen Martínez-Alcántara; Rodolfo Canet; Ana Quiñones (Agronomy, 2022)
The aim of this study was to establish DRIS (Diagnosis and Recommendation Integrated System) norms and Nutritional Optimal Ranges (NOR) for ‘Rojo Brillante’ Protected Designation of Origin (PDO) ‘Ribera del Xúquer’. The database contained 800 leaf samples collected in different crop phenological stages [after flowering (AF), fruit enlargement (FE), fruit colouring (FC), and harvesting HV)]. DRIS norms (78) were established for macronutrients: N, P, K, Ca, Mg and S; micronutrients B, Cu, Fe, Mn, and Zn and salinity elements: Na and Cl. The Nutrient Balance Index (NBI; the absolute value of the sum of the DRIS indices) was used to determine the optimal sampling period. Fruit enlargement was the period during which persimmon trees were more nutritionally balanced regardless of sprout origin (vegetative or floral) and irrigation type (drip or flood) in orchards